Exiles, displacements, and relocation through the trauma of birth in Anak, Barcelona, Dubai, and Milan - De Castro, Imelda (2020)
Access online through this link: https://www.plarideljournal.org/article/exiles-displacements-and-relocation-through-the-trauma-of-birth-in-anak-barcelona-dubai-and-milan
Keywords: Filipino foreign workers; Motion pictures; Film criticism